Substantiation of Proposals on Improvement of Normative and Legal Regulation in the Field of Pathogenic Biological Agents Handling in the Russian Federation - M. N. Lyapin; T. A. Kostyukova; I. Yu. Sukhonosov; M. V. Pchelintseva; A. V. Pomyaksheva; E. M. Golovko (Проблемы особо опасных инфекций, 2013)
Presented are the results of assessment of the national regulatory framework in the field of pathogenic biological agents handling in comparison with the same foreign one and WHO recommendations. Shown is the necessity of timely introduction of amendments or revision of the national regulatory documents. The topical issues requiring decision are specified. The proposals on improvement of normative legal regulations are submitted. The development of the common regulatory document integrating the issues of biological safety provision seems to be advisable.